Penggunaan Kartu Huruf dan Permainan Mencari Kartu Huruf Untuk Peningkatan Pengenalan Huruf - Muhamad Toha; Armyta Puspitasari; Ubaedillah Ubaedillah; Farhan Saefudin Wahid; Laelia Nurpratiwiningsih (LPPM Universitas Muhadi Setiabudi, 2020)
The purpose of this observation is to find out the increase in the ability to recognize letters in the children of group A PAUD Gemar Ilmu Regency of Brebes through letter card media. The subjects of this observation were group A children of 22 students. Data collection techniques are carried out through observation, checklist and interview. The results of the observation showed an increase in the ability to recognize letters in PAUD Gemar Ilmu students in group A after learning using letter card media, which initially was in the percentage of 45.44% to 86.26%. Thus the use of letter card media in learning to recognize letters can improve the ability to recognize letters in the children of group A PAUD Gemar Ilmu Regency of Brebes.